Histamine iontophoresis on the viability of random skin flap in rats - Esteves Junior, Ivaldo [UNIFESP] (2009)
PURPOSE: To evaluate the effects of the histamine iontophoresis on the random skin flap viability in rats. METHODS: Sixty adult male Wistar rats were used. A cranially-based dorsal skin flap measuring 10 x 4 cm was raised and a plastic barrier was placed between the flap and its bed. After the surgical procedure, the animals were randomized into four groups (G1-G4) (n=15 each group) as follows: G1 (control) - sham electrical stimulation, G2 (electrical stimulation) - direct current electrical stimulation, G3 (histamine) - histamine and sham electrical stimulation and G4 (histamine iontophoresis) - transdermal iontophoresis of histamine. In all groups the procedures were performed immediately after the surgery and on the two subsequent days. The percentage of flap necrosis was measured on the seventh postoperative day. RESULTS: The mean and the respective standard deviation of the percentage of flap necrosis areas were as follows: G1 (control) - 47.87 ± 9.13%, G2 - 51.49 ± 8.19%, G3 - 46.33 ± 8.32% and G4 - 30.82 ± 11.25%. The G4 group presented a significantly smaller amount of flap necrosis when compared to the other groups (p<0.001). CONCLUSION: The topical administration of the histamine by iontophoresis was effective to increase the viability of the random skin flaps in rats.